Effects of the Hot Water Pre-treatments and Storage Durations on the Seed Germination of Falcata (Falcataria Falcata (L.) Greuter & R. Rankin) (Bangladesh Journal of Botany, 2024)
Seed dormancy in Falcataria falcata (L.) Greuter & R. Rankin is well documented. In order to attain a higher seed germination rate, the effect of hot water pre-treatment and storage duration was determined in this study. This study found a highly significant difference (p < 0.05) between the mean Cumulative Germination Percentage (CGP) between treatments. Hot water pre-treatment significantly increased the CGP of seeds. However, storage duration and its interaction with different hot water pre-treatment did not have a statistically significant effect on the CGP of seeds. Overnight (12 hrs) soaking of seeds in water with an initial temperature of 80oC yields the highest CGP regardless of the storage duration. On development, it was found that radicle emergence of imbibed seeds generally starts within 1-2 days.Bangladesh J. Bot. 53(2): 249-255, 2024 (June)